1995
DOI: 10.1103/physrevlett.74.1371
|View full text |Cite
|
Sign up to set email alerts
|

Equation of State and Shear Strength at Multimegabar Pressures: Magnesium Oxide to 227 GPa

Abstract: The equation of state, elasticity, and shear strength of magnesium oxide were examined to 227 GPa using synchrotron x-ray diffraction in a diamond anvil cell. Static compression, ultrasonic elasticity, and shock data for MgO from ambient pressure to above 200 GPa can all be described by a single Birch-Murnaghan equation of state when the static shear strength, which is determined to be at least 11 GPa at 227 GPa, is taken into account. Our results show that there are significant changes in the degree and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
164
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(188 citation statements)
references
References 18 publications
18
164
0
6
Order By: Relevance
“…The estimated St for each data point is listed in Table I. In our P-V-T data set, the St value ranges from −0.0020 to 35 ͒ and its pressure dependence for Au and Pt is unknown, we cannot directly estimate the deviatoric stress in the sample. For reference, Shim et al 36 reported the ͉St͉ value of CaSiO 3 perovskite at P = 18-96 GPa and T = 1238-2419 K ranged from −0.005 to 0.005.…”
Section: A Experimental Resultsmentioning
confidence: 99%
“…The estimated St for each data point is listed in Table I. In our P-V-T data set, the St value ranges from −0.0020 to 35 ͒ and its pressure dependence for Au and Pt is unknown, we cannot directly estimate the deviatoric stress in the sample. For reference, Shim et al 36 reported the ͉St͉ value of CaSiO 3 perovskite at P = 18-96 GPa and T = 1238-2419 K ranged from −0.005 to 0.005.…”
Section: A Experimental Resultsmentioning
confidence: 99%
“…Figure 7 and Table 4 show the results obtained for the P-V-T equation of state of periclase, as compared to different kinds of experimental data (i.e., static compression in the diamond-anvil cell, ultrasonic measurements, etc.) [89][90][91][92][93][94][95][96][97], semi-empirical modelling of experimental data [98][99][100] and other DFT [59,61,101] and MD [60,84] calculations. The EOS of MgO has been calculated according to Equation (15) in a range of conditions compatible with those realized in the Earth's lower mantle (i.e., P = 0-160 GPa, V/V 0 = 0.65-1.00, T = 0-3000 K).…”
Section: P-v-t Equation Of State (Eos)mentioning
confidence: 99%
“…Lower mantle thermodynamics and rheology are thus largely controlled by periclase and its Fe-bearing analogue (ferropericlase) [16,[107][108][109][110]. (14) and (15) Calculated results of this work are compared to selected experimental data obtained by hydrostatic or quasi-hydrostatic compression in the diamond-anvil cell [90][91][92][93] and ultrasonic measurements [94][95][96][97]. The results of semi-empirical assessments [98,100], other ab initio LDA [59], GGA [61] and empirically-corrected GGA [101] calculations and MD simulations [60,84] are also shown for comparison.…”
Section: P-v-t Equation Of State (Eos)mentioning
confidence: 99%
“…At ambient conditions MgO crystallises in the NaCl ("B1") structure that type, which is remarkably stable: this is the only structure that has ever been observed for MgO, although experiments have explored pressures up to 227 GPa [20] and all the way up to the melting temperature. It is expected that under extreme pressure the CsCltype ("B2") structure will become stable, but the best theoretical calculations [21][22][23][24][25] indicate that the pressure of such a transition is very high, $510 GPa.…”
Section: Periclase (Mgo)mentioning
confidence: 99%